The Cash Ceiling : Why Only the Rich Run for Office--and What We Can Do about It - Carnes, Nicholas, 1984- (Book collections on Project MUSE., 2018)
Why are Americans governed by the rich? Millionaires make up only three percent of the public but control all three branches of the federal government. How did this happen? What stops lower-income and working-class Americans from becoming politicians? This book is a compelling and comprehensive account of why so few working-class people hold office - and what reformers can do about it. It debunks popular misconceptions (like the idea that workers are unelectable or unqualified to govern), identifies the factors that keep lower-class Americans off the ballot and out of political institutions, and evaluates a variety of reform proposals. The book shows that in the United States elections have a built-in "cash ceiling," a series of structural barriers that make it almost impossible for the working-class to run for public office. Elections take a serious toll on candidates, many working-class Americans simply cannot shoulder the practical burdens, and civic and political leaders often pass them over in favor of white-collar candidates. But these obstacles are not inevitable. Pilot programs to recruit, train, and support working-class candidates have the potential to increase the economic diversity of our governing institutions and ultimately amplify the voices of ordinary citizens. Who runs for office goes to the heart of whether the USA has a democracy that is representative or not. The book shows that the best hope for combating the oversized political influence of the rich might simply be to help more working-class Americans become politicians